Informing policy and practice on insect pollinator declines: Tensions between conservation and animal welfare - Barrett, Meghan; Fischer, Bob; Buchmann, Stephen (Frontiers in Ecology and Evolution, 2023)
Climate change, agricultural intensification, and other anthropogenic ecosystem challenges have caused declines in the diversity and abundance of insect pollinators. In response to these declines, entomologists have called for greater attention to insect pollinator conservation. Conservation primarily aims to protect groups of non-human animals—populations or species—with only secondary concern for the welfare of individual animals. While conservation and animal welfare goals are sometimes aligned, they often are not. And because animal welfare comes second, it tends to be sacrificed when in tension with conversation priorities. Consider, for example, lethal sampling to monitor many pollinator populations. Growing evidence suggests that the welfare of individual insect pollinators may be morally significant, particularly in the Hymenoptera and Diptera. Considering insect welfare in conservation practices and policies presents many challenges as, in the face of rapid, anthropogenic change, it may be impossible to avoid harming individual animals while promoting diverse populations. We suggest some practical, implementable strategies that can allow for more robust integration of animal welfare goals into insect pollinator conservation. By following these strategies, entomologists may be able to find policies and practices that promote the health of ecosystems and the individual animals within them.